E-Consultancy: Shifting towards Digital Intelligence - Yadav, Minakshi (INTERNATIONAL JOURNAL OF RESEARCH IN EDUCATION METHODOLOGY, 2013)
This paper represents the application of e-consultancy in the fields heath sector, engineering and education. Here we are representing the analytical study of the impact of e-consultancy in all the above sectors. In education sector e-consultancy is used for making learning more effective and interesting for students.In health sector it is used in emergency and online consult to doctor.In field of engineering to design projects and to implements algorithms. At the end we are concluding the benefits of e-consultancy services